2022
DOI: 10.3390/ijms231911491
|View full text |Cite
|
Sign up to set email alerts
|

Jellyfish Polysaccharides for Wound Healing Applications

Abstract: Jellyfishes are considered a new potential resource in food, pharmaceutical and biomedical industries. In these latter cases, they are studied as source of active principles but are also exploited to produce marine collagen. In the present work, jellyfish skin polysaccharides (JSP) with glycosaminoglycan (GAG) features were extracted from Rhizostoma pulmo, a main blooming species of Mediterranean Sea, massively augmented by climate leaded “jellyfishication” of the sea. Two main fractions of R. pulmo JSP (RP-JS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In 2022, Migone et al isolated new polysaccharides (JSPs) from the jellyfish Rhizostoma pulmo. These polysaccharides have typical glycosaminoglycan (GAG) structures, confirmed by LC-MS techniques, such as glucose, galactose, glucosamine and galactosamine, also presented in Figure 4 [135]. This jellyfish is one of the main prolific species in the Mediterranean and the Black Sea.…”
Section: Polysacharides From Jellyfish (Jsp)mentioning
confidence: 73%
See 1 more Smart Citation
“…In 2022, Migone et al isolated new polysaccharides (JSPs) from the jellyfish Rhizostoma pulmo. These polysaccharides have typical glycosaminoglycan (GAG) structures, confirmed by LC-MS techniques, such as glucose, galactose, glucosamine and galactosamine, also presented in Figure 4 [135]. This jellyfish is one of the main prolific species in the Mediterranean and the Black Sea.…”
Section: Polysacharides From Jellyfish (Jsp)mentioning
confidence: 73%
“…Its two main fractions were isolated from Rhizostoma pulmo (RP-JSPs): a neutral fraction (RP-JSP1) and a sulfate-rich fraction, (RP-JSP2), with average molecular weights of 121 kDa and 590 kDa, respectively. Migone et al demonstrated the importance of these compounds in wound healing by applying the in vitro scratch test [135]. The results confirmed that both RP-JSP polysaccharides show good activity in tissue regeneration, achieving cell proliferation of more than 80% [135].…”
Section: Polysacharides From Jellyfish (Jsp)mentioning
confidence: 88%
“…As the only precedent of this work, Fernández-Cervantes et al showed the preparation of a cell-free scaffold from jellyfish Cassiopea andromeda , but did not investigate the effects of different decellularization methods and test the biocompatibility and functions of the jellyfish matrix in vivo . 43 Compared to the scaffolds fabricated with the collagen purified from jellyfish, 27,39–42 matrices obtained through decellularization are not only easy to prepare but also can better preserve the natural 3D structure as well as many potentially bioactive components of the jellyfish ECM. In this study, the decellularized jellyfish matrix exhibited promising biocompatibility and a capacity to facilitate wound healing in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…48 Fourth, the polysaccharides in the jellyfish matrix might also be beneficial for wound repair. 39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation